Development of safe navigation system for tidal restriction area - Mahmud, Mohd. Razali; Tengku Ali, Tengku Afrizal (2006)
The sea moves: the land usually stays still. As seawater is dynamic, vessel navigation will be difficult without any equipment or guidance such as Global Positioning System (GPS), Nautical Chart, Electronic Chart Display and Information System (ECDIS) or even any of the aid to navigation system. ECDIS are rapidly gaining popular acceptance as powerful for increasing navigational safety and augmenting situational awareness. However, most of the ECDIS do not represents the actual depth of water. It is the goal of this study to develop a system that will be able to update the water depth depending on tidal levels at given date and time, with various sizes of vessels draft and determines locations of the sea that is safe for vessels to sail through. Although there are several factors that should be taken into account to ensure the under keel clearance is adequate, this study focuses on the draft only as a main factor. Other factors that may cause the changes in under keel clearance are excluded .This system was developed using Microsoft Visual Basic 6.0, and Map Objects 2.0 to visualize the spatial data and with tidal data prediction in Microsoft Access database. Therefore, users without Geographic Information System (GIS) exposure can easily use this system. Mapping technique in GIS added an excellent visualizing, which can provide information in decision making in order to know the right passage without jeopardize the vessels. The output of this system is a map showing locations of the sea that has sufficient depth levels for vessels with different sizes to sail through. Safe depths are marked as blue points and locations without safe depths are marked with red points. For planning purposes, tide required calculation can be made and this will produce a graph showing the times of sufficient tide in blue and times of insufficient tide in red. The result, while still requiring work (especially on ship navigation), would be an improvement in port safety because the actual depth of water and safely navigable area for a vessel of particular draft is displayed on the system in real time and can be of assistance especially at tidal restriction area.